Large Mucocele of the Appendix at Laparoscopy Presenting as an Adnexal Mass in a Postmenopausal Woman: A Case Report. (6th April 2014) - Paladino, Elvira; Bellantone, Maria; Conway, Francesca; Sesti, Francesco; Piccione, Emilio; Pietropolli, Adalgisa
Abstract : A 79-year-old female was referred to our Gynecologic Department presenting with a pelvic magnetic resonance imaging (MRI), showing an adnexal mass, later confirmed at the pelvic examination. The patient's routine laboratory tests were normal. A sonographic examination was performed with inconclusive results. Although the ultrasonography excluded the presence of vascularization and malignant degeneration, the adnexal localization appeared to be dubious. The laparoscopy and the subsequent histologic examination revealed the presence of a mucocele of the appendix. The following case report focuses the attention on a misdiagnosis of appendiceal mucocele. The misdiagnosis caused no negative impact on the treatment that in this case was adequate and successful.